Antioxidant Activity of Tempeh Ethanolic Extract on Male Swiss Mouse Brain - Yohanes Dwiatmaka; Nunung Yuniarti; Endang Lukitaningsih; Subagus Wahyuono (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
Tempeh is an Indonesian food made of soybean (Glycine max (L.) Merr.) by fermentation using Rhizopus spp mold. Soybean has a high content of protein, fatty acids, vitamins, and isoflavone glycosides. Isoflavone glycosides are poorly absorbed in the human intestine. Fermentation hydrolyzes isoflavone glycosides into isoflavone aglycones which are easily absorbed. Soybean has three main isoflavones, they are genistein, daidzein, and glycitein. They are good antioxidants and have estrogen-like activity. This research studies the antioxidant activity of tempeh ethanolic extract by determining the concentration of superoxide dismutase (SOD) and glutathione peroxidase (GPx) in the brain tissue of male Swiss mice. All test substances were diluted in 0.5% CMC-Na solution and administered orally once daily for 12 days. The 0.5 mL of 15% ethanol solution (16.67 mL/kg BW) was administered 1 hour before the other substances. Tempeh ethanolic extract (500 mg/kg BW) as the main treatment. Donepezil-HCl (1 mg/kg BW) and genistein (2.55 mg/kg BW) were used as the positive control groups. The mouse brain SOD and GPx concentration were determined on the 13th day. Results showed a significant depletion of SOD and GPx concentration by ethanol administration. Compared to the control group, mice with tempeh ethanolic extract showed no significant change in the GPx concentration but a little decrease in SOD. The SOD in the group of tempeh ethanolic extract was significantly higher than in the group of donepezil-HCl and genistein. Briefly concluded that tempeh ethanolic extract has better antioxidant activity than donepezil-HCl and genistein.